Designing a Point-Based Skincare Packaging Recycling Model Through Design Thinking: Implications for Educational Management - Hana Rania Shaliha; Dinda Azahra Ichwan; Nurul Fitri Tiara; Asep Taryana (Journal of Educational Management Research, 2026)
This study aims to design a point-based skincare packaging recycling model using the Design Thinking approach to address the persistent intention–action gap in consumer recycling behavior. The research also explores how circular business practices can be integrated into educational management, particularly in sustainability education and green campus initiatives. A mixed-methods design was employed, combining a survey of 60 consumers with semi-structured interviews involving local skincare SMEs. The Theory of Planned Behavior and circular economy principles were used to analyze the roles of awareness, perceived ease, incentives, and behavioral intention. Results indicate that although environmental awareness is high (≈95%), actual recycling participation is low (16%). Accessibility barriers and insufficient incentives emerged as the strongest predictors of participation intention. Through iterative Design Thinking stages, this study developed the Circular Chain Return & Reward (CCRR) model, which incorporates QR-based tracking, drop-point networks, point rewards, and transparent digital reporting. Simulation findings show that more than 90% of respondents would participate when convenience and tangible rewards are provided. The model offers managerial implications for skincare SMEs and educational institutions by strengthening sustainability management, increasing stakeholder engagement, and supporting curriculum or program development related to environmental responsibility.